The nature of work-family conflict and it's relationship with psychological health outcomes - Gilham, Candice Anne (Department of Psychology, 2015)
This study examined the nature and psychological health outcomes of work-family conflict amongst South African corporate employees from two organisations in the Western Cape (N = 160). Cross-sectional data was obtained via self-report questionnaires. Exploratory factor analysis evidenced the bi-directionality of work-family conflict, work-to-family conflict (W2FC) and family-to-work conflict (F2WC). Contrary to expecting a multidimensional model in each direction, exploratory factor analyses showed that W2FC was a unidimensional construct. However in the direction F2WC, a time and strain dimensions was found supporting its multidimensionality. Using standard multiple regression analysis, W2FC explained a significant proportion of the variance in psychological strain (i.e. anxiety and depression) and burnout (exhaustion and depersonalisation). Interestingly F2WC did not explain a significant proportion of variance in any of the psychological health outcomes. These results show that pressures arising in the work domain negatively influence employees' wellbeing. These results are discussed and management implications presented.